Crystal Structure of (1r,5s)-9-Nitro- 1,2,3,4,5,6-Hexahydro-1,5- Methanopyrido[1,2-A][1,5]Diazocin-8-One (9-Nitrocytisine), c11h 13o3n3 - Saez-Briones, P (Sociedad Chilena de Quimica, 2011)
The title compound (1, trivial name: 9 (or 3)-nitrocytisine) crystallizes with two independent molecules in the asymmetric unit. In its structure two rings form a bispidine framework that is fused to a 3-nitro-2-pyridone group. The half-normal probability plot reveals that the two molecules do not show any significant geometrical differences, except in conformations of the nitro-group, which is involved in intermolecular interactions. The crystal packing structure of the title compound is described in terms of three-dimensional supramolecular arrays built up from chains of N-H?O (nitro-group), hydrogen bonds and weak intermolecular C-H?O=C interactions, with graph-set descriptors C2 2(6) and C2 2(10) motifs, which together result in R4 4(26) rings motifs. These chains are additionally stabilized by intermolecular NO2?? interactions.